Starch accumulation dynamics and transcriptome analysis of Chlorella sorokiniana during transition of sulfur nutritional status - Xu, Haiqing; Yang, Jinzhi; Wang, Xu; Peng, Qing; Han, Yanxia; Liu, Xudong; Liu, Kexin; Dou, Shijuan; Li, Liyun; Liu, Guozhen; Yang, Ming (Frontiers in Marine Science, 2022)
Microalgae can effectively accumulate starch by using nutritional limitation methods in the context of bioalcohol fuel production. However, relatively few studies have focused on starch accumulation in microalgae and its molecular basis, especially under sulfur limitation conditions. In this study, the starch accumulation dynamics and physiological responses of Chlorella sorokiniana under sulfur starvation (SS) and sulfur replenishment (SR) conditions were investigated, and the genes involved in the transcriptional regulation were explored using RNA-seq. The starch content in C. sorokiniana cells significantly increased from 1.6% to 55.0% of dry weight within 24 h under SS conditions, and then, it decreased to 3.4% within 12 h after transition to SR conditions. However, cell growth was inhibited, and pigment content decreased under SS conditions. Using RNA-seq analysis, a total of 9720 differentially expressed genes (DEGs) induced by sulfur status were obtained. These genes were narrowed down to 454 starvation and replenishment cross-validated (SRV)-DEGs, among which 283 SRV-DEGs were significantly up-regulated and 171 SRV-DEGs were down-regulated under SS conditions, and returned to their previous state under SR conditions. The SRV-DEGs enriched in the sulfate metabolism pathway were all up-regulated under SS conditions after 6 h to speed up the sulfur metabolic cycle, and the transcriptional abundance of a sulfate transporter (SULTR4), cysteine synthase[O-acetylserine(thiol)-lyase] (OASTL), serine acetyltransferase (SAT), and methanethiol oxidase (SELENBP1) increased 8.6-fold, 12.6-fold, 8.7-fold, and 12.4-fold, respectively. Protein synthesis was correspondingly inhibited, which resulted in the reallocation of carbon and elevated the starch synthesis pathway, in which the expressions of glycogen branching enzyme (GBE) and starch synthase (SS) were up-regulated 12.0- and 3.0-fold, respectively. The fatty acid desaturase (FAD) and phosphatidic acid phosphatase (PAP) in the lipid synthesis pathway were strongly up-regulated 8.8- and 16.2-fold, respectively, indicating the competitive synthesis of lipids. The down-regulation of SRV-DEGs associated with carbon fixation, such as those in the Calvin cycle, possibly affected cell growth. The time-resolved transcriptional analysis identified the SRV-DEGs, revealing the underlying starch accumulation mechanism, as well as the relationship with cell growth and lipid synthesis.